Molecular genetic mapping of NIR spectra variation - Diepeveen, Dean; Clarke, G.; Ryan, K.; Tarr, A.; Ma, W.; Appels, R. (2011)
A novel analytical approach was used to identify associations between Near-Infrared (NIR) spectral fingerprints and segments of wheat (Triticum aestivum L.) chromosomes indicating the location of genetic factors contributing to variation in NIR spectra. To identify the genetic factors, environmental and experimental variability were removed from the spectra using spatial mixed models. These corrected spectra were combined with the molecular genetic analysis of wheat lines from a structured population derived from a Carnamah by WAWHT2046 doubled haploid set of progeny. The association of chromosome segments with specific NIR wavelengths was established using all-subset regression and canonical correlation methodology. These improved processes for analysing NIR spectra were validated using 161 lines in breeding trials analysed over a period of 3 years across 40 sites.